Educational Method in the Quran: Analysis of Islamic Education Science Surah An-Nahl Verse 125 - Muhammad Syauqi Mubarok; Reski Ramadhani; Marissa Disthy Putri (International Journal of Islamic Khazanah, 2023)
This research is entitled "Educational Method in the Quran Surah An-Nahl Verse 125 (the Analysis of Islamic Education Science)". This study aims to figure out the educational method contained in the Quran Surah An-Nahl verse 125. The method used was the descriptive-qualitative analysis method. The data were collected through library research from various sources, i.e. commentary books, educational science books, papers, and educational, scientific journals. The study revealed that the concept of educational methods contained in the Quran Surah An-Nahl verse 125 is the Hikmah, mau'izhah, and Jadil methods. The implications of these three methods in teaching and learning activities in schools are, first, the hikmah method can be synchronized with the lecture method. Second, the mau'izhah method can be applied in guidance and counselling sessions as a curative or repressive measure when a normative or procedural violation occurs and as a preventive measure where educators can use the mau'izhah session in the form of messages or appeals at the end of each learning session. Third, the Jadil method can be used to improve existing discussion methods.